2015
DOI: 10.1007/s11238-015-9510-3
|View full text |Cite
|
Sign up to set email alerts
|

Egalitarian–utilitarian bounds in Nash’s bargaining problem

Abstract: For every 2-person bargaining problem, the Nash bargaining solution selects a point that is "between" the relative (or normalized) utilitarian point and the relative egalitarian (i.e., Kalai-Smorodinsky) point. Also, it is "between" the (non-normalized) utilitarian and egalitarian points. I improve these bounds. I also derive a new characterization of the Nash solution which combines a bounds property together with strong individual rationality and an axiom which is new to Nash's bargaining model, the sandwich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…1;2 In a previous paper, Rachmilevitch (2015), I provided an alternative proof of the aforementioned betweenness. In that paper, as well as in Rachmilevitch (2016), I showed that the Nash solution, in several senses, is closer to utilitarianism than it is to egalitarianism. In particular, I showed how the portion of the Pareto frontier that ranges from the utilitarian point to the egalitarian point can be meaningfully divided into two parts, and the Nash point lies in the part closer to the utilitarian choice.…”
Section: Introductionmentioning
confidence: 89%
“…1;2 In a previous paper, Rachmilevitch (2015), I provided an alternative proof of the aforementioned betweenness. In that paper, as well as in Rachmilevitch (2016), I showed that the Nash solution, in several senses, is closer to utilitarianism than it is to egalitarianism. In particular, I showed how the portion of the Pareto frontier that ranges from the utilitarian point to the egalitarian point can be meaningfully divided into two parts, and the Nash point lies in the part closer to the utilitarian choice.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, it balances fairness and efficiency, which is a tradeoff and compromise between egalitarianism and utilitarianism. Moreover, the Nash bargaining solution is demonstrated to be more utilitarian than egalitarian (Rachmilevitch, 2016). That is, it puts more emphasis on utilitarianism than egalitarianism.…”
Section: Construction Of Value Functions For Different Principlesmentioning
confidence: 99%
“…It is based on the principle of maximizing the product of players' surplus utilities, applicable to bargaining scenarios when negotiators with personal preferences are motivated to achieve proportionate cooperation (MacCrimmon & Messick, 1976). The Nash bargaining solution is "between" the utilitarian and egalitarian points (Rachmilevitch, 2016). Therefore, it balances fairness and efficiency, which is a tradeoff and compromise between egalitarianism and utilitarianism.…”
Section: Construction Of Value Functions For Different Principlesmentioning
confidence: 99%
See 1 more Smart Citation